New Zealand blackcurrant extract enhances muscle oxygenation during forearm exercise in intermediate-level rock climbers - Fryer, S.; Paterson, C.; Perkins, I. C.; Gloster, C.; Willems, M. E.; Potter, J. A. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The delivery to and utilization of oxygenated hemoglobin to the forearm muscles are key determinants of rock-climbing performance. Anthocyanin-rich New Zealand blackcurrant (NZBC) has been suggested to improve blood flow and may enhance forearm endurance performance. As such, a double-blind, randomized crossover design study with 12 participants performed submaximal intermittent contractions (at 40% maximal voluntary contraction) to failure after a 7-day intake of 600 mg/day NZBC extract or placebo. Minimum tissue saturation index (TSI%) was assessed during the contractions. During recovery, time to half recovery of TSI% and brachial artery blood flow were assessed. There was no difference in time to exhaustion between NZBC and placebo. Minimum TSI% was lower with NZBC extract (43 ± 8 vs. 50 ± 11 TSI%; p = .007; Cohen`s d = 1.01). During recovery, there was no effect on brachial artery blood flow. However, time to half recovery was faster with NZBC (26 ± 17 vs. 42 ± 26 s; p = .001; Cohen`s d = 1.3) following exhaustive contractions. Seven days of NZBC extract appears to improve muscle oxygenation during and following contractions with no change in either arterial blood flow or forearm endurance performance.